2007
DOI: 10.1111/j.1872-034x.2007.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus natural recombinant RF1_2k/1b strain among intravenous drug users in Uzbekistan

Abstract: In conclusion, the finding of RF1_2k/1b in Central Asia indicates that the variant has wide geographic distribution. The PCR-based screening method developed in this study should be useful in further epidemiological and clinical studies on the recombination phenomenon in HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 27 publications
(42 reference statements)
0
43
1
1
Order By: Relevance
“…The reported recombinant was cautiously designated RF1_2k/1b, in agreement with the nomenclature used for human immunodeficiency virus (HIV) recombinants [124] . This same recombinant strain has since then been isolated in other countries, like Ireland [125] , Uzbekistan [126] , Cyprus [127] , France [128] and Estonia [129] which would suggest that, although its generation might not be favoured by natural selection, it would also not be selected against [49] . Additionally, at least ten other different intergenotypic recombinant forms (RFs) of HCV have been described and are totally or partially characterised (Table 1).…”
Section: Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported recombinant was cautiously designated RF1_2k/1b, in agreement with the nomenclature used for human immunodeficiency virus (HIV) recombinants [124] . This same recombinant strain has since then been isolated in other countries, like Ireland [125] , Uzbekistan [126] , Cyprus [127] , France [128] and Estonia [129] which would suggest that, although its generation might not be favoured by natural selection, it would also not be selected against [49] . Additionally, at least ten other different intergenotypic recombinant forms (RFs) of HCV have been described and are totally or partially characterised (Table 1).…”
Section: Recombinationmentioning
confidence: 99%
“…Finally, despite recombination events between different genotypes/subtypes co-infecting the same patient are probably easier to detect, they are less likely to occur, since the strains of different subtypes differ more between them than between those from the same subtype; this would imply a lower probability of template switching and moreover, if a recombination event does indeed happen, it will likely generate recombinant sequences less viable than the parental ones. Some or even all these factors acting in concert might explain why the frequency of recombinant HCV sequences reported to date is so low [49,111,[124][125][126][127][128][129][130][131][132][133][134][135][136][137][140][141][142][143][144][145][146][147] . How relevant recombination for HCV long term evolution and its incidence in HCV infection is, has not been thoroughly investigated yet, but these findings support a potentially significant role for recombination by creating genetic variation through the reshuffling of independent variants [146] .…”
Section: Recombinationmentioning
confidence: 99%
“…Because of this huge genetic diversity, HCV is currently classified into six major genotypes and more than 80 subtypes (44). Recombination may be another mechanism exploited by HCV to increase genetic diversity: naturally occurring intergenotypic recombinant viruses that often have their recombination points in the trans-membrane domains of NS2 were recently identified (20,21,26,27,33,35).…”
mentioning
confidence: 99%
“…Because of this huge genetic diversity, HCV is currently classified into six major genotypes and more than 80 subtypes (44). Recombination may be another mechanism exploited by HCV to increase genetic diversity: naturally occurring intergenotypic recombinant viruses that often have their recombination points in the trans-membrane domains of NS2 were recently identified (20,21,26,27,33,35).Recent publications have reported the presence of natural HCV subgenomic RNAs in serum and liver of infected patients, mostly containing large in-frame deletions from E1 up to NS2, always found together with the full-length wild-type (wt) RNAs (5,16,36,54). These mutant viral genomes persist for a long time (at least 2 years), and sequence analysis suggests that subgenomic (the predominant species during this period) and full-length HCV evolve independently (54).…”
mentioning
confidence: 99%
“…Limiting productive coinfection reduces the chances of recombination between HCV strains and the transfer of drug resistance or adaptive mutations between viral strains. Indeed, intra-and intergenotypic recombinant strains of HCV are rare even among patients with multiple infections (54)(55)(56), although a few examples have been detected (57)(58)(59)(60)(61). Interestingly, it has been suggested that coinfection with multiple strains of HCV leads to exacerbation of chronic HCV disease correlates (62).…”
Section: Discussionmentioning
confidence: 99%